Property in Social Continuity - von Benda-Beckmann, F. (Brill, 1979)
This book deals with the property and inheritance system of the matrilineal Minangkabau of West Sumatra in the context of legal pluralism.
English
Keywords: Asian history; indonesia; Adat; Matrilineality; Minangkabau people; Netherlands; Sharia